Studentâs Satisfaction in Doing Assessment by Using Lasvita - Fitria, Yuanovita Prihatianti; Ngadiso, Ngadiso; Sumardi, Sumardi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
When final examination (UNBK) by using conventional assessment tends to facilitate cheating, another offer in language learning assessment has been done, i.e., computer-based test. However this test has weakness, because it is only held at school because of the server connection reason. One of the solution being proposed here is having assessment by using Lasvita. Lasvita itself, is an android-based program which is designed to help teachers both do teaching and assessing. The easiness to organize, manage, practical, and support eco-learning makes Lasvita is considered to give satisfaction for students in doing assessment. This research will dig up more the satisfaction of the students by using questionnaire. Quantitative method will be used, while for analyzing data, satisfaction index theory will also be employed here. Describing the details of the research, it is expected that this research will give a reference for schools to do an effective assessment in language learning.